Polysaccharide and Protein Films with Antimicrobial/Antioxidant Activity in the Food Industry: A Review - Jamróz, Ewelina; Kopel, Pavel (Polymers, 2020)
From an economic point of view, the spoilage of food products during processing and distribution has a negative impact on the food industry. Lipid oxidation and deterioration caused by the growth of microorganisms are the main problems during storage of food products. In order to reduce losses and extend the shelf-life of food products, the food industry has designed active packaging as an alternative to the traditional type. In the review, the benefits of active packaging materials containing biopolymers (polysaccharides and/or proteins) and active compounds (plant extracts, essential oils, nanofillers, etc.) are highlighted. The antioxidant and antimicrobial activity of this type of film has also been highlighted. In addition, the impact of active packaging on the quality and durability of food products during storage has been described.
Keywords: antimicrobial and antioxidant activity; polysaccharide; food packaging systems; protein; composite materials; biopolymer films; nanofillers; plant extracts; active packaging materials; essential oil